P Pembuatan Gambar Kerja dan Rencana Anggaran Biaya (RAB) Jalan Desa Tambak Sirang Darat: Creation of Working Drawings and Budget Plan (RAB) for the Tambak Sirang Darat Village Road - Afandi, Ahmad; Nurrohman, Muhammad Farid; Norhayati, Putri; Fathul, Fathul; Mukti, Jamaludin Surgi; Noor, Muhammad Ori Rianta; Masruroh, Silfiana Ila; Priadikusumah, Ginanjar (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2025)
The development of village road infrastructure is a major factor in improving connectivity and the economy of the community. This study aims to create working drawings and prepare a Cost Budget Plan (RAB) for a road construction project in Tambak Sirang Darat Village. The planning process begins with a field survey to collect technical data, such as existing road conditions, topography, and material requirements. Furthermore, working drawings are created using civil engineering software to ensure the design meets the appropriate road pavement standards. The RAB is calculated based on a unit price analysis of the work, which includes the costs of materials, labor, and tools. The results of the study indicate that systematic planning in creating working drawings and cost estimates can help manage resources efficiently, reduce the potential for budget overruns, and ensure that construction runs according to technical specifications. It is hoped that the results of this study can be a reference in the implementation of more effective and sustainable village road projects.